EDUCATIONAL CONTENT ON TIKTOK: ENGAGEMENT AND COMMUNICATION STRATEGY - Yohanes Michael Christanto (Juremi: Jurnal Riset Ekonomi, 2026)
TikTok has evolved not only as an entertainment platform, but also as medium for disseminating educational content supporting digital marketing communication strategies. However, research on educational content on TikTok remains limited, especially content characteristics and audience engagement patterns. This study aims to analyze the characteristics of educational content on TikTok and the resulting engagement pattern. The research uses descriptive qualitative methods using content analysis. Data were collected from non-participative observation on ten highly engaging educational contents on TikTok published between June and December 2025. The result shows that educational content is prominently presented in a talking-head or solo podcast style supported by on-screen text or closed caption (CC). In addition, content is delivered in a casual and easily understandable style, and provides concrete examples and applicable steps. The engagement pattern indicates that audience engagement is not only reflected in likes, but also saves, shares, and comments as more highly valuable forms of interaction. Practical and applicable content tends to generate higher numbers of saves and shares, while reflective content, especially on mental health topics generates more audience comments. These findings emphasize that educational content on TikTok serves as an effective digital marketing communication strategy in building audience engagement and closeness.